Peran Literasi Digital dalam Memfilter Informasi dan Konten Hoaks di Media Sosial - Sarasvati, Priska; Siswadi, Gede Agus (Samsara Institute Publisher, 2025)
As time goes by, technological advances are also growing rapidly until new media are created, one of which is social media. Social media is a place where people can interact, communicate and share information virtually, and this is where people can use it to share information and content that they produce and own. However, the information and content circulating on social media is not necessarily true or can be said to be hoax news, so to anticipate this, digital literacy is needed. In this research the author will discuss fake news or hoax news and low literacy, the role of social media in disseminating content and information, and the importance of digital literacy. This research uses a qualitative research method with descriptive research type, for the data collection method the author uses literature study (library study). The results of this research are the importance of digital literacy in filtering information and content on social media and the factors that cause low digital literacy in society can also be identified. literacy, not only that, with this research we can also find out the media for distributing information and content that is often used by the public.